Efecto de diferentes métodos de multiplicación de leguminosas herbáceas (Stizolobium aterrinum, Georgina velvet, y Canavalia ensiformis) sobre calidad nutricional del forraje - Chabesta Correa, Carlos Andrés (2023)
With the objective of determining the effect of different methods of multiplication of herbaceous legumes on the nutritional quality of the forage produced, a study was carried out at the National Institute of Agricultural Research (INIAP) Portoviejo Experimental Station. Components, fresh biomass, dry matter and seed yield were determined; likewise, the chemical composition of the whole plant was studied. The sowing distance and methods used for herbaceous legumes had a marked influence on the responses of morphological indicators and yield in fresh and dry biomass, where variability was shown for morphological indicators with the best results for trellis cultivation for S. aterrinum at 1 m from planting distance with 92 leaves, C. ensiformis with 28.30 cm width of the leaves. While, for yields it was higher for the crop without stakes at 1.00 m in the species C. ensiformis with 8.45 a 32.62 t.ha-1 of green matter and 0.84 a 5.68 t.ha-1 of dry matter produced. The grains were greater for the cultivation with stakes in the species C. ensiformis at 1.0 m of planting of one meter with 3.45 t.ha-1, the crude protein was better for C. ensiformis with the use of trellises at 0.5 m and crude fiber and ash for S. aterrinum for sowing in soil at 1 m distance with 52.76 and 7.12%. It is concluded that the distance and planting method has a marked effect on the growth, production and nutritional quality of these species according to the ages of regrowth.